2017
DOI: 10.5539/ijbm.v12n5p27
|View full text |Cite
|
Sign up to set email alerts
|

Instructor Acceptance of Mobile Learning in Saudi Arabia: A Case Study of Hail University

Abstract: Mobile technology has influenced almost every aspect of our modern lives. The enhancement of learning in Saudi Arabia, as well as significant development in education overall, may be possible through mobile learning. However, the successful implementation of mobile learning in tertiary education profoundly relies on the acceptance of mobile learning from both students and instructors. Most mobile learning acceptance studies target higher education students. Therefore, this study aimed at examining the factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 8 publications
5
9
0
Order By: Relevance
“…Therefore, H 2 was accepted. This finding supports the research conducted by [32], [33]. Earlier, a study by [32] devices believe it can be a learning tool to help improve learning outcomes.…”
Section: B Assessment Of Structural Modelsupporting
confidence: 90%
See 3 more Smart Citations
“…Therefore, H 2 was accepted. This finding supports the research conducted by [32], [33]. Earlier, a study by [32] devices believe it can be a learning tool to help improve learning outcomes.…”
Section: B Assessment Of Structural Modelsupporting
confidence: 90%
“…Therefore, H 4 was rejected. Several previous studies have shown results that are in line with the studies conducted [33], [35]. Studies by [33] show that facilitating conditions is not a key factor for educators to implement quality teaching involving MT.…”
Section: B Assessment Of Structural Modelsupporting
confidence: 80%
See 2 more Smart Citations
“…With regard to students perceived 'mobile learning acceptance, findings seem to suggest eight key factors that influence the adoption of m-learning by higher education students in Saudi Arabia. These include performance expectancy, effort expectancy, facilitating conditions, social influence , environmental factors, nature of the institution's leadership, technological, access, organisational, and individual [21], [22]. While the other factors that influence the adoption of m-learning by higher education students in developed countries such as Japan, Korea, Australia and UK include perceived convenience, perceived ease of use and perceived usefulness, instant connectivity, compatibility, interaction, content enrichment, and computer self-efficacy, influencing the perceived usefulness of Technology Acceptance Model (TAM) [23], [24], [25].…”
Section: Q2 What Are the Most Common Factors Influencing The M-learnmentioning
confidence: 99%